Istinbath Maslahah Mursalah Method in Economics - Marisa Rizki; Moh Bahrudin; Syamsul Hilal (Al-Fadilah: Islamic Economics Journal, 2024)
. The Maslahah Mursalah  istinbath method is an Islamic legal approach used to determine rulings on issues not explicitly addressed in the Qur'an and Hadith. In the field of economics, this method aims to establish policies that promote public welfare (Maslahah) and prevent harm (mudarat), in alignment with Sharia principles. This study seeks to understand the application of this method in economic contexts by identifying problems, analyzing benefits and harms, and formulating relevant solutions. The findings indicate that the Maslahah Mursalah method is effective in providing contextual and adaptive solutions to modern economic developments, as long as they remain within Sharia boundaries. This approach emphasizes a balance between individual benefits and collective interests, making it relevant to addressing contemporary economic challenges.